Estimating the number of regular and dependent methamphetamine users in Australia, 2002-2014. - Degenhardt, L.; Larney, S.; Chan, G.; Dobbins, T.; Weier, M.; Roxburgh, A.; Hall, W.; McKetin, Rebecca (Australasian Medical Publishing, 2016)
Objective: To estimate the number of regular and dependent methamphetamine users in Australia. Design: Indirect prevalence estimates were made for each year from 2002–03 to 2013–14. We applied multiplier methods to data on treatment episodes for amphetamines (eg, counselling, rehabilitation, detoxification) and amphetamine-related hospitalisations to estimate the numbers of regular (at least monthly) and dependent methamphetamine users for each year. Dependent users comprised a subgroup of those who used the drug regularly, so that estimates of the sizes of these two populations were not additive. Results: We estimated that during 2013–14 there were 268 000 regular methamphetamine users (95% CI, 187 000–385 000) and 160 000 dependent users (95% CI, 110 000–232 000) aged 15–54 years in Australia. This equated to population rates of 2.09% (95% CI, 1.45–3.00%) for regular and 1.24% (95% CI, 0.85–1.81%) for dependent use. The rate of dependent use had increased since 2009–10 (when the rate was estimated to be 0.74%), and was higher than the previous peak (1.22% in 2006–07). The highest rates were consistently among those aged 25–34 years, in whom the rate of dependent use during 2012–2013 was estimated to be 1.50% (95% CI, 1.05–2.22%). There had also been an increase in the rate of dependent use among those aged 15–24 years (in 2012–13 reaching 1.14%; 95% CI, 0.80–1.69%). Conclusions: There have been increases over the past 12 years in the numbers of regular and dependent methamphetamine users in Australia. Our estimates suggest that the most recent numbers are the highest for this period, and that the increase has been most marked among young adults (those aged 15–34 years).